The determinants of relationship between gross domestic product growth and growth of factors of inflation, import, export and foreign direct investment / Nur Fatin Amira Md Yunus - Md Yunus, Nur Fatin Amira (2018)
Economic performance of the country is symbolizing the success of the nation. In order to measure the economic performance of the country is using the most effective tool which is gross domestic product (GDP). Generally, gross domestic product is to measure the total value that produce by the country from all people including the government and companies. In many countries, Malaysia as developing country has shown their economic performance in a good way. The gross domestic product can be affected by many factors to determine whether the economic is growth or downtrend. Therefore, the relationship between the factors is taking into the purpose of the study. It is to identify the factors have positive or negative relationship between the factors and the gross domestic product. Hence, the study will be conduct throughout yearly collection of data from 1971 to 2017 with the total Observation is 47. The gross domestic product growth will be the dependent variable of the study while inflation, import. export and foreign direct investment will be the factors of independent variable. Based on the previous study, the relationship of gross domestic product and the factors is expected to be negative relationship with inflation, positive relationship with import, negative relationship with export and negative relationship with foreign direct investment.